2018
DOI: 10.22270/ujpr.v3i5.198
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Activity of Jatropha Tanjorensis Leaves

Abstract: The term “wound” is defined as a disruption of normal anatomical structure. Therefore, “healing” is the complex and dynamic process that results in the restoration of anatomical continuity and function. Albino Wistar rats (150-180 g) of both sexes were selected. The experiment of Wound Healing Activity by Excision Wound Model and Incision Wound Model by the simple ointment B.P., reference standard drug (0.2% w/w nitrofurazone ointment), stigmasterol ointment (0.2% w/w), hexane, chloroform and methanol extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Moreover, Hujiahemaiti et al reported that quercetin promotes the proliferation of human oral keratinocytes via upregulation of adhesion molecules and increases the re-epithelization rate of keratinocytes [30]. Stigmasterol, one of the most abundant plant sterols, displays various pharmacological and biological activities, such as antioxidant and anti-inflammatory activities [31], and stigmasterol ointment accelerates wound healing in animal models [32]. The ethanolic extract of G. procumbens also contained terpenes, which have a variety of properties, including antimicrobial, anti-inflammatory, antioxidant and wound healing activities [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hujiahemaiti et al reported that quercetin promotes the proliferation of human oral keratinocytes via upregulation of adhesion molecules and increases the re-epithelization rate of keratinocytes [30]. Stigmasterol, one of the most abundant plant sterols, displays various pharmacological and biological activities, such as antioxidant and anti-inflammatory activities [31], and stigmasterol ointment accelerates wound healing in animal models [32]. The ethanolic extract of G. procumbens also contained terpenes, which have a variety of properties, including antimicrobial, anti-inflammatory, antioxidant and wound healing activities [33,34].…”
Section: Discussionmentioning
confidence: 99%